Adapting to terrace housing living in Malaysia - Abdul Rahim, Zaiton; Hashim, Ahmad Hariza (Elsevier, 2012)
This paper attempted to examine the behavioural adaptation in relation to the Malay culture namely the activity system, privacy and social interaction of the Malay families and terrace housing modification. The study employs case studies involving 11 Malay families living in the three-bedroom two-storey terrace houses in two urban locations in Malaysia. Findings indicate that behavioural adaptation resulted in changes in some aspects of the Malay culture and housing modifications may have provided a more supportive living environment but have adverse effects on individual family and housing community due to the constraints of the existing housing design.